Private schools vs state schools in Argentina : Discipline or citizenship? - Vicente, María Eugenia (2017)
This paper aims to review the link between public education policies on social inclusion and the institutional practices in state-run and private secondary schools in Argentina in the current context of compulsory secondary education. The methodology used is in line with socio-educational management studies oriented to analyze educational practices qualitatively from an institutional perspective. The data was collected through 28 semi-structured interviews with state and private secondary school headmasters, and supplemented by the analysis of relevant documents. The contributions hereto prove that, in practice, discipline and citizenship are not compatible goals at secondary school. Secondary schools are either oriented towards the control and punishment of behaviours that deviate from the objectives set by a minority (as is clearly shown in private educational management), or towards the collective discussion of decisions and agreements (as clearly shown in state educational management). This has direct implications on the analysis of the success of education policies on social inclusion at secondary school being realized through compulsory education. The results of this piece of research go beyond the quantitative analysis about how many students graduate from school, to include the issue of the social relevance of secondary school training processes. Particularly, it is not just a matter of quantity, but of whom and how are youths and adolescents trained at secondary schools.
Keywords: Education policies; State and private schools; Social inclusion; Enseñanza pública; Enseñanza privada; Política educacional; Argentina